1997
DOI: 10.1007/bf02466394
|View full text |Cite
|
Sign up to set email alerts
|

Determination of triazine herbicides by capillary gas chromatography with large-volume on-column injection

Abstract: SummaryThis paper describes a study of the potential of largevolume on-column injection for the determination of triazine herbicides in clean water samples (groundwater). The sensitivity of chromatographic determination has been increased by two orders of magnitude by injection of up to 200 gL of pesticide solutions and nitrogen-phosphorus detection. Analytical characteristics expressed as precision, linear range and limit of detection have been determined, the results indicating adequate analytical performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…In this process, large-volume injection techniques offer suitable ways like direct water injection or in-vial extraction. Several applications of both methods have been described during recent years [1][2][3][4][5]. In a previous paper [6] the behaviour of water in a PTV injector during speed-controlled large-volume injection was demonstrated by means of a transparent model injector.…”
Section: Introductionmentioning
confidence: 99%
“…In this process, large-volume injection techniques offer suitable ways like direct water injection or in-vial extraction. Several applications of both methods have been described during recent years [1][2][3][4][5]. In a previous paper [6] the behaviour of water in a PTV injector during speed-controlled large-volume injection was demonstrated by means of a transparent model injector.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been shown that HADPs constitute the most important fraction of the atrazine residues found in soil (16,25) The higher pK a values of these metabolites (HADPs pK a ) 4-5; atrazine pK a ) 2) may allow them to establish mixedmode binding mechanisms based on hydrophobic and cationicexchange interactions with soil components, while atrazine and its chlorinated metabolites are limited to hydrophobic interactions (26). Environmental monitoring of these metabolites is based on chromatographic techniques such as high-performance liquid chromatography with ultraviolet detection (HPLC/UV) or gas chromatography with mass spectrometry identification (GC/MS) after organic solvent extraction followed by purification/ concentration steps (7,(27)(28)(29). Due to their high polarity and water solubility, an important drawback of these procedures is the low efficiency of the procedures for extraction from aqueous samples (water solubility data: atrazine, 0.15 mM; HA, 0.24 mM; DEA, 2 mM; DIA, 1.20 mM; DEDIA, DEHA, and DIHA, >2 mM) (30)(31)(32).…”
Section: Introductionmentioning
confidence: 99%
“…Different approaches are available for achieving large-volume injection in capillary GC: on-column injection [1][2][3][4], programmed temperature vaporization (PTV) injection [5][6][7][8][9], or splitless injection with solvent elimination [ 10,11 ]. Thus, the combination of microextraction procedures with LVI in GC seems a powerful tool in the analysis of organic micropollutants in water.…”
Section: Introductionmentioning
confidence: 99%